2020
DOI: 10.3892/ol.2020.11533
|View full text |Cite
|
Sign up to set email alerts
|

Elevated mRNA expression levels of DLGAP5 are associated with poor prognosis in breast cancer

Abstract: Breast cancer is the most commonly diagnosed type of cancer and one of the leading causes of cancer-associated mortality in women. In addition, the underlying molecular mechanisms of the occurrence and development of breast cancer requires further investigation. In the present study, bioinformatics analysis was performed to identify differentially expressed genes (DEGs) between breast cancer and normal breast tissues to investigate the underlying molecular mechanisms. In addition, reverse transcription-quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 62 publications
(61 reference statements)
1
25
0
Order By: Relevance
“…Although it remains to be fully elucidated what the exact functional contributions of HURP in the mitotic spindle assembly are, the strong evidence mentioned above provides important insights into the role of HURP in the control of cell cycle. Importantly, as expected, the upregulated of HURP in many common cancers is detected, including HCC [8,14], bladder cancer [15], prostate cancer [16,17], breast cancer [18,19], lung cancer [20,21], colorectal cancer [22], as well as endometrial carcinoma [23], but not in normal tissues, indicating that misregulation of its expression plays roles in carcinogenesis.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Although it remains to be fully elucidated what the exact functional contributions of HURP in the mitotic spindle assembly are, the strong evidence mentioned above provides important insights into the role of HURP in the control of cell cycle. Importantly, as expected, the upregulated of HURP in many common cancers is detected, including HCC [8,14], bladder cancer [15], prostate cancer [16,17], breast cancer [18,19], lung cancer [20,21], colorectal cancer [22], as well as endometrial carcinoma [23], but not in normal tissues, indicating that misregulation of its expression plays roles in carcinogenesis.…”
Section: Introductionsupporting
confidence: 70%
“…An increased number of studies have con rmed that DLGAP5 Upregulated occurs in many cancer tissues as mentioned in the introduction. DLGAP5/HURP is initially found to be upregulated in HCC by bioinformatics analysis, and the results subsequently con rmed by experiments [7], In a similar way, its Upregulated in many cancers is found by analysis of database or microarray data and experimental veri cation, such as prostate cancer [16,17], breast cancer cells [19], lung cancer [20,21], and endometrial carcinoma [23]. In the present study, our TCGA pan-cancer analysis clearly showed signi cant upregulated of DLGAP5 in at least 26 types of cancer tissues compared with the respective adjacent tissues (P < 0.001), including ccRCC, and 7 types mentioned above.…”
Section: Discussionmentioning
confidence: 69%
“…DLGAP5 and CDC7 are potential cell cycle regulators that play roles in carcinogenesis of cancer cells. Elevated expressions of DLGAP5 were noticed in breast cancer specimens and were associated with poor prognosis [29]. Moreover, a cellular apoptosis susceptibility protein (CSE1L), is extensively expressed in certain types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that these genes are involved in the pathogenesis of LUAD. For instance, the prognostic value of DLGAP5 has been assessed in other cancers, such as colorectal cancer (37), pancreatic cancer (38) and breast cancer (39). Prior studies on LUAD have also identi ed prognostic signatures including DLGAP5 (40); however, little is known about how this gene affects the development of LUAD (41,42).…”
Section: Discussionmentioning
confidence: 99%